Influence of Temperature of Heat Reservoir on Performance of Regenerative Room- temperature Magnetic Ericsson Refrigeration Cycle - 张艳; 俞炳丰; 高强; 王从飞 (Zhileng xuebao)
On the basis of the molecular- field theory and thermodynamics of magnetic system, the relation between heat and magnetic entropy change of the regenerative room - temperature magnetic Ericsson refrigeration cycle was analyzed in our study. Moreover, the influence of the temperature of heat reservoir on the performance of ferromagnetic magnetic Ericsson refrigeration cycle was investigated. The numerical simulation for the magnetic refrigeration cycle with typical ferromagnetic material Gadolinium was conducted. The results show that there will be an important turn of the cycle performance near the Curie temperature. Whenever temperature is higher than Curie temperature, only the condition of occurs, otherwise, both conditions appear. In addition, the maximum of high- temperature heat reservoir increases with the increase of low- temperature heat reservoir. And for the same heat reservoir, the increase rate ofde-creases while magnetic field strength increases.